Coronavirus atau virus corona merupakan keluarga besar virus yang menyebabkan infeksi saluran pernapasan atas ringan hingga sedang, seperti penyakit flu. Banyak orang terinfeksi virus ini, setidaknya satu kali dalam hidupnya. Namun, beberapa jenis virus c - Fattatul Awaliyah (Iqtishodiah: Jurnal Ekonomi dan Perbankan Syariah, 2021)
The general public has extensive experience in conventional-based banking and has little or no understanding of Islamic banking products and systems. In addition, there are still too few Islamic bank units compared to conventional banks so that many people do not really understand or understand the service products offered and the Islamic banking system. This type of research is an associative quantitative type, the researcher conducts research that is a relationship between two variables, while the form of the researcher uses a casual relationship, namely the relationship caused by consequences. In this study, there are independent variables (variables that affect) and dependent (). The conclusion of this research is that strategic marketing mix has an effect on public interest which can be seen from the answers to the questionnaire given to the public, that people are starting to look at Islamic banking but are still constrained by its promotion.